Analysis of Lateral Shifting of Slab on Pile on Soft Soil in Coastal Area - Friendly Alexander Ambarita; Trihanyndio Rendy Satrya; Ria Asih Aryani Soemitro (Interdisciplinary Social Studies, 2025)
This study discusses the settlement and lateral displacement of piles on a toll road built on saturated soft soil in a coastal area. The case study focuses on the point where the off-ramp and main road meet, with soil conditions dominated by very soft clay to a depth of ±58 m (N-SPT <10), meaning the piles function primarily as friction piles. Soil data from the BH-03 drill were processed through N-SPT correction, consistency grouping, and compressibility parameter correlation to obtain input for numerical modeling. The modeling was done using PLAXIS 2D under plane strain conditions, with the Soft Soil model for clay and Mohr–Coulomb for non-cohesive soil. Construction stages included 2.5 m of backfilling, two years of consolidation, and the installation of new piles near existing piles. The results showed that the vertical settlement of the pile tip from the numerical model was 3.9 cm, closely matching the analytical calculation results (3.07–3.66 cm), which is still within the SNI 8460 serviceability criteria. However, the lateral displacement reached 5–5.7 cm, exceeding the SNI limit of <2.5 cm. Horizontal displacement contours revealed a 6.3–10.1 cm soil shift toward the outside of the slope during new pile construction, indicating that long-term consolidation, embankment slope geometry, and seabed slope are the main causes of lateral deformation.